Penerapan Pembelajaran Matematika Model Kooperatif Tipe Team Games Tournament untuk Meningkatkan Hasil Belajar Siswa di Lingkungan Pondok - Rosyidi, Moh. Farhan Irgiawan; Kurniawan, Agus Prasetyo; Sulaikah (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to examine the effect of implementing the cooperative learning model Team Games Tournament (TGT) on students’ mathematics learning outcomes in a boarding school environment. The study was motivated by the low motivation and participation of students in mathematics learning, which tends to be monotonous. This research employed a pre-experimental method with a One Group Pretest–Posttest design. The participants were 32 seventh-grade students of SMPN 3 Peterongan. A mathematics learning achievement test (pretest and posttest) was used to measure students’ learning improvement after the implementation of the TGT model. Data were analyzed using the Kolmogorov–Smirnov and Shapiro–Wilk normality tests and the Wilcoxon Signed Rank test. The findings revealed that the average pretest score of 65.63 increased to 90.00 on the posttest. The Wilcoxon Signed Rank test produced a Z value of 4.990 with a p-value < 0.001, indicating a highly significant difference between students’ learning outcomes before and after the treatment. These results demonstrate that the TGT cooperative learning model is effective in improving students’ mathematics learning outcomes. Moreover, the model fosters an engaging and interactive learning atmosphere and encourages active student participation. This study is expected to serve as a reference for teachers to apply more varied and innovative learning strategies to enhance students’ motivation and achievement.